Pemetaan Indeks Kesuburan Tanah pada Lahan Budidaya Bawang Merah di Kelurahan Mataran Kabupaten Enrekang: Mapping of Soil Fertility Index in Shallot Cultivation Land in Mataran Village, Enrekang Regency - Idul; Burhanuddin Rasyid (Jurnal Ecosolum, 2025)
Background. Mataran Village is a shallot-producing area in Enrekang district whose production is recorded to decline every year. The decline is suspected to be due to cultivation techniques on sloping land so that it can affect the level of soil fertility, especially in chemical properties. The importance of soil fertility information in the form of geospatial data presented by soil fertility index maps. Objective. Mapping the soil fertility index of shallot cultivation land in Mataran village, Anggeraja District. Method. The research uses descriptive and quantitative methods based on the Soil Fertility Index (SFI) class according to Santoso et al. (2010), in the form of a survey with purposive sampling and then analysis in the laboratory. The parameters observed were Cationic Exchange Capacity (KTK), Exchangeable Bases (Ca-dd, Mg-dd and K-dd), P-available, N-total, C-Organic, Al Saturation, and soil pH. Results. 15 has an SFI value of 160 classified as a Rather Low (AR) class, T2, T5, T6, T7, T8, T9, T11, T12, T13, T14, T16 has an SFI value of 165 – 200 classified as a Medium class (S), T1, T3, T4, T10, has an SFI value of 205 – 215 and is classified as a Rather High (AT) class, there are three SFI classes presented in the distribution map. Conclusion. Shallot cultivation land in Mataran village, Anggeraja district has an SFI value of 160-215 which is classified as a Rather Low to Somewhat High criterion located in Sossok and Belalang hamlets with limiting factors such as KTK, P-available, K-dd, and Mg-dd.